(untitled) (Italiano LinguaDue, 2022)
Il contributo presenta le attività svolte sul testo letterario nell’ambito del progetto LeCo (2019-2021), dedicato al problema della comprensione della lettura negli studenti della scuola secondaria di secondo grado. Si illustrano le premesse teoriche, le applicazioni e alcuni risultati, in un quadro di ricerca che metta a frutto i rapporti tra educazione letteraria ed educazione linguistica. Per indagare sulle competenze degli studenti e provare a migliorarle, infatti, è necessario ripartire dal “valore d’uso” della letteratura, dalle sue specificità, ma anche dalla centralità della lingua. A survey of literary text comprehension: applications, findings, and research perspectives The paper outlines the activities carried out about the literary text within the LeCo project (2019-2021), dedicated to the problem of reading comprehension for secondary school students. The theoretical premises, applications, programs and some preliminary results are illustrated, within a research framework that enhances the relationships between literary education and language education. In order to study the students’ skills and try to improve them, in fact, it is necessary to start from the “use value” of literature and its specificities, but also from the central role of language.